The Influence of the Fraud Hexagon Theory Factors on the Financial Statement Fraud of Companies in the Transportation and Logistics Sector - Putu Sarita Nareswari; Ni Luh Sari Widhiyani (International Journal of Management Research and Economics, 2025)
This study aims to examine the influence of fraud hexagon theory factors on financial statement fraud in transportation and logistics sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The fraud hexagon theory elements in this study are proxied by financial targets, ineffective supervision, auditor changes, board of directors changes, frequency of CEO photo appearances, and State-Owned Enterprises. The sample in this study was 19 companies that had been selected using purposive sampling techniques. The number of observations in this study was 95 observations. The data analysis carried out in the study was panel data regression analysis using EViews 12 software as a data analysis tool. The results of the analysis showed that financial targets had a positive effect on financial statement fraud. However, ineffective supervision, auditor changes, board of directors changes, frequency of CEO photo appearances, and state-owned enterprise variables were shown to have no effect on financial statement fraud. This study provides theoretical implications in the form of additional information about the influence of financial targets on financial statement fraud and this study also provides practical implications for company leaders to pay more attention and consider the company's financial targets as one of the indicators that can be used to detect financial statement fraud.